Neural Stem Cells and Methods for Their Generation From Induced Pluripotent Stem Cells in vitro - Galiakberova, Adelya A.; Dashinimaev, Erdem B. (Frontiers in Cell and Developmental Biology, 2020)
Neural stem cells provide promising approaches for investigating embryonic neurogenesis, modeling of the pathogenesis of diseases of the central nervous system, and for designing drug-screening systems. Neural stem cells also have an application in regenerative medicine. The most convenient and acceptable source of neural stem cells is pluripotent stem cells (embryonic stem cells or induced pluripotent stem cells). However, there are many different protocols for neural induction and differentiation of neural stem cells, and these result in a wide range of neural cell types. This review is intended to summarize the knowledge accumulated by researchers in this field to date. It should be useful for researchers who are beginning investigations in this area of cell biology.